Engagement in Culturally and Regionally Relevant Physical Activity (Hula, Outrigger Paddling, Spearfishing, and Surfing) in the State of Hawai‘i Over the Lifecourse: A Cross-Sectional Analysis - Catherine McLean Pirkle; Mika D. Thompson; Rebekah Rodericks; Simone M. Schmid; Lance Kaeo Ching; Mele A. Look; Yan Yan Wu; Michael M. Phillips; Tetine Lynn Sentell (Journal of Physical Activity and Health, 2026)
Background : Culturally and regionally relevant physical activities (CRRPA) show promise for disease prevention and strengths-based public health promotion. Understanding engagement across the lifecourse can support effective public health policy, research, and practice. This study examined: (1) factors associated with lifetime CRRPA participation; (2) contexts of practice and the frequency and duration of engagement; and (3) lifetime participation in 4 CRRPA in Hawai‘i (Hula, outrigger canoe paddling, spearfishing, and surfing). Methods : A cross-sectional analysis was conducted among 1044 English-speaking adults in Hawai‘i. Native Hawaiians (NH) and residents of primarily rural islands (not O‘ahu) were oversampled for representation. Lifetime participation in each CRRPA was self-reported and dichotomized. Engagement was characterized by sociodemographic and health-related variables. Frequency, context, and duration were summarized for the total sample and for NH (n = 425). Engagement patterns over the lifecourse are also presented. Results : 69.3% of respondents reported lifetime engagement in at least one CRRPA: 44.9% engaged in Hula, 41.4% in surfing, 34.9% in spearfishing, and 33.9% in outrigger canoe paddling. Most respondents participated in multiple CRRPA; 12.4% engaged in all 4 at some point in their lives. Among NH, family-based participation was common, especially for spearfishing and surfing. The mean session duration for all activities was 2 hours or more, with more frequent engagement reported among NH. Engagement was highest during earlier life stages and declined with age. Trends varied notably by generation. Conclusions : Engagement in CRRPA is widespread across Hawai‘i, underscoring opportunities to advance strengths-based public health promotion, planning, and policy for health equity.